Implemetação em hardware da máquina virtual lua - (:unkn) unknown (Universidade Federal do Pampa, 2013)
The constant advancement of the manufacturing processes of integrated circuits has ena-bled the development of computational systems increasingly complex. Currently has been highlighting the embedded systems that gain space and market in products of electronics con-sumer. This work presents the proposal an architecture for a Dedicated Processor for execut-ing a set of instructions of form native of the language Lua 5.1, without the need use Lua virtual machine. The processor aims applications where the requirement of area is fundamen-tal, as embedded systems or systems integrated on a single chip - System on a Chip (SoC), and where it is not necessary to use powerful processors, in other words, whose applications are simple. Initially, after a literature review, where is presented characteristics of embedded systems and the Lua language, besides showing the formats and types of Lua instructions, a test program is presented in order to define a set of instructions to be implemented in the ded-icated processor. After is made the description organizational of processor, where is presents the element or group of elements required to implement the instruction set defined from the test program. Following are presented the data paths for each instruction defined previously. The results shown are the results of logic synthesis processor. The software used for logic synthesis was the Quartus II 9.1 Web Edition from Altera Corporation, and the synthesis was performed for the device Cyclone II FPGA EP2C35F672C6. Finally, in appendix is showed the code generated code after compiling test program, that was been described in language Lua.

Electrical engineering

Integrated circuits

Embedded systems

Hardware
Keywords: Engenharia elétrica; Circuitos integrados; Sistemas embarcados; Hardware; CNPQ::ENGENHARIAS